(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern linguistics the issue of euphemization in proverbs and sayings has not been studied in detail. Therefore the given issue requires a special consideration. The present article considers the issues of the components modification in proverbs and sayings in individual speech and discusses if the euphemization is preserved in this case.